Epigenetic control of mesenchymal stem cells orchestrates bone regeneration - Wang, Xiaofeng; Yu, Fanyuan; Ye, Ling (Frontiers in Endocrinology, 2023)
Recent studies have revealed the vital role of MSCs in bone regeneration. In both self-healing bone regeneration processes and biomaterial-induced healing of bone defects beyond the critical size, MSCs show several functions, including osteogenic differentiation and thus providing seed cells. However, adverse factors such as drug intake and body senescence can significantly affect the functions of MSCs in bone regeneration. Currently, several modalities have been developed to regulate MSCs’ phenotype and promote the bone regeneration process. Epigenetic regulation has received much attention because of its heritable nature. Indeed, epigenetic regulation of MSCs is involved in the pathogenesis of a variety of disorders of bone metabolism. Moreover, studies using epigenetic regulation to treat diseases are also being reported. At the same time, the effects of epigenetic regulation on MSCs are yet to be fully understood. This review focuses on recent advances in the effects of epigenetic regulation on osteogenic differentiation, proliferation, and cellular senescence in MSCs. We intend to illustrate how epigenetic regulation of MSCs orchestrates the process of bone regeneration.